KONDISI TERUMBU KARANG DI PERAIRAN SEKITAR AREA BEROPERASINYA PERUSAHAAN TAMBANG BATU BARA (STUDI KASUS: PKP2B PT. KALTIM PRIMA COAL, KUTAI TIMUR) [Coral Reef Condition in Waters Surrounding Operational Site of Coal Mining Company (Case Study: PKP2B PT. - Omega Raya Simarangkir; Firmansyah Tawang; Irwan .; Ayub .; Sila Kartika Sari; Derta Prabuning (BERITA BIOLOGI, 2022)
The condition of coral reefs is influenced by natural and anthropogenic factors. Anthropogenic activities such as coal mining will eventually have an impact on the surrounding ecosystems including coral reefs. This study aims to determine the condition of coral reefs in the waters around the operating areas of coal mining companies. This study is a preliminary study as a database that provides data on the health of coral reefs in the vicinity of the operation of mining companies in East Kutai Regency. Data was collected at Bengalon Reef, Kellie’s Reef and South Marker in March 2019 using Reef Check method, focusing on three indicators namely substrate, fish, and invertebrate. The line transect used in this method is 100 m long and divided into 4 segments. Physical and chemical parameters of the waters measured are current speed, brightness, pH, salinity, and water temperature. The condition of coral reefs in the study location is in medium category. The quality of the waters is in tolerance range of life support and coral growth. Indicator fish found were Chaetodontidae, Lutjanidae, Scaridae and Serranidae. Indicator invertebrates found were Holothuria edulis, Panulirus sp. and Tridacna spp. The dominant coral reef damage was found in boat anchors and fishing nets rubbish.